Vascular development and hemodynamic force in the mouse yolk sac - Garcia, Monica D.; Larina, Irina V. (Frontiers in Physiology, 2014)
Vascular remodeling of the mouse embryonic yolk sac is a highly dynamic process dependent on multiple genetic signaling pathways as well as biomechanical factors regulating proliferation, differentiation, migration, cell-cell and cell-matrix interactions. During this early developmental window, the initial primitive vascular network of the yolk sac undergoes a dynamic remodeling process concurrent with the onset of blood flow, in which endothelial cells establish a branched, hierarchical structure of large vessels and smaller capillary beds. In this review, we will describe the molecular and biomechanical regulators which guide vascular remodeling in the mouse embryonic yolk sac, as well as live imaging methods for characterizing endothelial cell and hemodynamic function in cultured embryos.